Pengaruh Reward dan Punishment Terhadap Produktivitas Kerja Karyawan PT Alfamart Cabang Masbagik - Fitriani, Elis; Shoilhah, Isfi (Alpatih Harapan Semesta, 2024)
Abstract: This study aims to determine the effect of reward and punishment on employee work productivity at PT Alfamart Masbagik branch. The research method used in this study is quantitative research. The population in this study were 30 Alfamart employees at the Masbagik branch. The sample used in this study was Probability Sumpling. Data collection techniques and instruments in this study used questionnaires, observation and documentation. The analysis method used is statistical analysis consisting of classical assumption tests, multiple linear regression analysis, hypothesis testing, coefficient of determination, validity tests and reliability tests. The results of this study indicate that 1) Rewards partially have a significant positive effect on employee work productivity, this can be seen from the calculated t value> t table (5.845> 2.051) with a significant level of 000 <0.05. 2) Punishment partially has a significant positive effect on employee work productivity, this can be seen from the calculated t value> t table (2.776> 2.051) with a significant level of 000 <0.05. 3) Reward and punishment simultaneously have a significant positive effect on work productivity, this can be seen from the calculated f value> f table (481.203> 3.35). So it can be concluded that partially or simultaneously reward and punishment have a positive and significant effect on employee work productivity at PT Alfamart Masbagik branch, because the higher the level of reward and punishment owned, the better their entrepreneurial behavior will be.